2006
DOI: 10.1158/0008-5472.can-05-2447
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism by Which Mammalian Target of Rapamycin Inhibitors Sensitize Multiple Myeloma Cells to Dexamethasone-Induced Apoptosis

Abstract: Mammalian target of rapamycin (mTOR) inhibitors curtail cap-dependent translation. However, they can also induce post-translational modifications of proteins. We assessed both effects to understand the mechanism by which mTOR inhibitors like rapamycin sensitize multiple myeloma cells to dexamethasone-induced apoptosis. Sensitization was achieved in multiple myeloma cells irrespective of their PTEN or p53 status, enhanced by activation of AKT, and associated with stimulation of both intrinsic and extrinsic path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
69
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 47 publications
6
69
0
Order By: Relevance
“…[32][33][34] At first this may seem paradoxical, as rapamycin is reported to induce autophagy through inhibition of mTOR. 35 However, mTOR also reduces expression of a number of anti-apoptotic proteins, including Bcl-2 and Mcl-1.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34] At first this may seem paradoxical, as rapamycin is reported to induce autophagy through inhibition of mTOR. 35 However, mTOR also reduces expression of a number of anti-apoptotic proteins, including Bcl-2 and Mcl-1.…”
Section: Discussionmentioning
confidence: 99%
“…The mammalian target of rapamycin (mTOR) facilitates the assembly of the translation preinitiation complex. mTOR inhibition by rapamycin or its analogues has been shown to decrease protein synthesis (42).…”
Section: Discussionmentioning
confidence: 99%
“…Confirmation of a true regulatory effect of AKT on sensitivity was obtained when an activated AKT allele was stably transfected into U266 cells. This stably transfected myeloma line was considerably more sensitive in vivo to the antitumor effects of mTOR inhibition than its empty vector transfected control (Frost et al, 2004;Yan et al, 2006).…”
Section: Introductionmentioning
confidence: 96%
“…In a xenograft model, we showed that the mTOR inhibitor, CCI-779, was an effective anti-myeloma drug, inhibiting in vivo tumor growth of OPM-2, 8226 and U266 MM tumors (Frost et al, 2004;Yan et al, 2006). Interestingly, the level of AKT activity was correlated with antitumor response to CCI-779, with OPM-2, which expresses constitutively active AKT owing to a phosphatase and tensin homolog deleted on chromosome ten (PTEN) mutation (Hyun et al, 2000), being the most sensitive.…”
Section: Introductionmentioning
confidence: 99%